Multiresolution Time Domain Based Different Wavelet Basis Studies of Scattering of Planar Stratified Medium and Rectangular Dielectric Cylinder - Cao, Qunsheng; Tamma, Kumar K. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, several wavelet bases, namely, the Daubechies, the biorthogonal Coiflet, the Deslauriers-Dubuc interpolating functions, and the cubic spline Battle-Lemarie, are applied to the multiresolution time domain (MRTD) technique for planar stratified media and electromagnetic scattering. These MRTD schemes are studied via field expansions of the scaling functions in one-dimensional (1D) and two-dimensional (2D) cases. A rigorous treatment method for inhomogeneous media structures is given. We have focused here on the study of reflected and transmission coefficients for an electromagnetic wave propagation on a stratified slab media and the scattering width (SW) of a rectangular dielectric cylinder. The 1D propagation characteristics of single and periodical stratified media and the 2D scattering width of the MRTD schemes are compared with the results of the FDTD method. Finally, we describe the computational accuracy of the relative peaks and shifting position errors, via a comparison of the results of the MRTD scheme based on the different basis with those of the FDTD method.